Penile cutaneous horn-a rare case - Kumar Barolia, Dinesh; Sethi, Deepak; Sethi, Anjali; Jamana, Ram; Meena, Shanker; Rachhoya, Pinky (International Journal of Medical Research and Review, 2015)
Penile cutaneous horn is a horn like hyper-keratotic lesion over penis which is an unusual site and a rare case. We report a case of cutaneous horn of penis in age of 20 years which is also a rare presentation in this age group.